High dielectric coating for improving flashover strength, insulator and preparation method

By coating the cyanoethyl cellulose layer with changing gradient on the surface of the insulator, the problems of flashover strength and electric field uniformization along the surface of the insulator are solved, and the mechanical performance is improved and the electric field distribution is uniform, which is suitable for large-scale production.

CN119264767AActive Publication Date: 2025-01-07CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411366183.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-07
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

When the prior art improves the flashover intensity of the insulator along the plane, it is difficult to achieve uniformization of the electric field distribution and prevent local electric field distortion at the same time, and the filler doping method is likely to affect mechanical properties.

Method used

It adopts a high dielectric coating structure, including the bottom layer and the top layer, the bottom layer is an epoxy resin layer, and the top layer is composed of cyanoethyl cellulose layers with different degrees of substitution. It is regulated by the relative dielectric constant of gradient change to uniform the electric field on the surface of the insulator. This improves the flashover strength.

Benefits of technology

It effectively improves the flashover strength of the insulator along the surface, avoids local electric field distortion and mechanical strength reduction caused by filler doping, realizes uniformization of the electric field distribution, is suitable for insulator bodies of complex structures, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264767A_ABST
    Figure CN119264767A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of insulator surface flashover strength improvement, in particular to a high-dielectric coating for improving flashover strength, an insulator and a preparation method. The high dielectric coating comprises a bottom layer and a top layer located on the outer side of the bottom layer; the bottom layer is an epoxy resin layer, and the preparation raw material of the epoxy resin layer comprises epoxy resin; the top layer is a cyanoethyl cellulose layer, and preparation raw materials of the cyanoethyl cellulose layer comprise cyanoethyl cellulose with different substitution degrees; wherein the substitution degree of the cyanoethyl group in the cyanoethyl cellulose is 1-2.8, and the relative dielectric constant of the cyanoethyl cellulose layer is 4-20. The high dielectric coating adopts cyanoethyl cellulose of which the degree of substitution of cyanoethyl groups is gradually reduced from a high electric field region to a low electric field region, so that the corresponding relative dielectric constant is reduced in a gradient manner, the effect of uniformizing the electric field on the surface of the insulator is achieved, and the surface flashover strength is further effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of improving the surface flashover strength of insulators, and in particular to a high-dielectric coating for improving the flashover strength, an insulator and a preparation method thereof. Background Art

[0002] In many power equipment, the insulation structure plays both the role of electrical insulation and mechanical support, so solid insulating media must be used, making the gas-solid composite insulation structure widely used. For example, overhead transmission lines, metal-enclosed switchgear (GIS), gas-insulated transmission pipelines (GIL) and other equipment are all gas-solid composite insulation structures. However, due to the large difference in the dielectric properties of gas and solid, the electric field at the gas-solid interface is distorted, resulting in the surface flashover strength being much lower than the breakdown strength of gas and solid, which can easily cause surface flashover accidents of composite insulation. Therefore, improving the surface flashover strength is of great significance to ensure the safe operation of power equipment.

[0003] The electric field distortion at the gas-solid interface is an important reason for the reduction of the flashover intensity along the surface. Relevant scholars have proposed a variety of methods to uniformly distribute the electric field. Among them, constructing functional gradient materials with dielectric constants that vary with spatial position has important application prospects. The existing method is to dope BaTiO in insulating materials. 3 、TiO 2 High dielectric constant fillers can regulate the equivalent dielectric constant of composite materials, and changing the content of fillers can achieve effective regulation of the equivalent dielectric constant.

[0004] CN114502619B discloses a method for preparing a resin and a method for preparing an insulating structure, the method comprising: a filler mixing step of mixing a nano filler with an epoxy resin at a ratio of 15wt% or more to form a mixture; a shear mixing step of shear mixing the mixture; a diluent mixing step of mixing a reactive diluent that reduces the viscosity of the epoxy resin with the mixture after the shear mixing step; and a curing agent mixing step of mixing an acid anhydride curing agent with the mixture after the diluent mixing step. The nano filler contains a non-conductive metal oxide.

[0005] However, the filler doping method has the following problems: ① The dielectric constant of the doped filler is different from that of the insulating material itself. Although it can improve the equivalent dielectric constant of the composite material, it distorts the electric field strength at the filler-insulating material interface and easily reduces the breakdown strength of the composite insulating material; ② In order to obtain a high equivalent dielectric constant, the filler doping content is usually very high, which can easily affect the mechanical properties of the composite material.

[0006] Based on the above situation, the insulation structure of the existing power equipment cannot simultaneously achieve uniform electric field distribution and prevent local electric field distortion and reduction in mechanical strength, which are technical problems that need to be solved urgently. Summary of the invention

[0007] In order to solve the above-mentioned technical problems, the present invention provides a high dielectric coating for improving flashover strength, wherein the high dielectric coating comprises a bottom layer and a top layer located outside the bottom layer; The bottom layer is an epoxy resin layer, and the raw materials for preparing the epoxy resin layer include epoxy resin; The top layer is a cyanoethyl cellulose layer, and the raw materials for preparing the cyanoethyl cellulose layer include cyanoethyl cellulose with different degrees of substitution; The substitution degree of cyanoethyl groups in cyanoethyl cellulose is 1-2.8, and the relative dielectric constant of the cyanoethyl cellulose layer is 4-20.

[0008] Furthermore, the cyanoethyl cellulose layer is divided into three overlapping sections: a first section of a high-substituted cyanoethyl cellulose layer, a second section of a medium-substituted cyanoethyl cellulose layer, and a third section of a low-substituted cyanoethyl cellulose layer. The thickness of the first high-substituted cyanoethyl cellulose layer is greater than that of the second medium-substituted cyanoethyl cellulose layer, and the thickness of the second medium-substituted cyanoethyl cellulose layer is greater than that of the third low-substituted cyanoethyl cellulose layer.

[0009] Furthermore, the thickness of the high dielectric coating gradually decreases from the high electric field region to the low electric field region, that is, the thickness of the high dielectric coating gradually decreases from the first section of the high-substituted cyanoethyl cellulose layer to the second section of the medium-substituted cyanoethyl cellulose layer, and then decreases from the second section of the medium-substituted cyanoethyl cellulose layer to the third section of the low-substituted cyanoethyl cellulose layer.

[0010] Furthermore, the maximum thickness of the top layer does not exceed 1 mm.

[0011] Furthermore, the thickness of the bottom layer is 50-200um.

[0012] Furthermore, in the first section of the high-substitution degree cyanoethyl cellulose layer, the degree of substitution of cyanoethyl groups in cyanoethyl cellulose is greater than 2.4 and less than or equal to 2.8, and the relative dielectric constant is greater than 13 and less than or equal to 20; In the second section, the degree of substitution of cyanoethyl groups in the cyanoethyl cellulose layer is greater than 1.6 and less than or equal to 2.4, and the relative dielectric constant is greater than 7 and less than or equal to 13; The degree of substitution of cyanoethyl groups in the cyanoethyl cellulose in the third low-substituted cyanoethyl cellulose layer is greater than or equal to 1 and less than or equal to 1.6, and the relative dielectric constant is greater than or equal to 4 and less than or equal to 7.

[0013] Furthermore, the coating lengths of the first section of the high-substituted cyanoethyl cellulose layer, the second section of the medium-substituted cyanoethyl cellulose layer and the third section of the low-substituted cyanoethyl cellulose layer are equal.

[0014] Furthermore, the first section of the high-substituted cyanoethyl cellulose layer is located at the triple junction formed by the electrode, the solid and the gas.

[0015] Furthermore, the epoxy resin is bisphenol A glycidyl ether.

[0016] Furthermore, the raw materials for preparing the epoxy resin layer also include a curing agent.

[0017] Furthermore, the curing agent is one of methyl tetrahydrophthalic anhydride, phthalic anhydride, methyl hexahydrophthalic anhydride and phthalic anhydride.

[0018] Furthermore, the raw materials for preparing the epoxy resin layer also include an accelerator.

[0019] Furthermore, the promoter is 2,4,6-triphenol.

[0020] Furthermore, when the raw materials for preparing the bottom layer include epoxy resin, curing agent, and accelerator, the mass ratio of epoxy resin, curing agent, and accelerator is (100-110): (70-90): (1-20).

[0021] The present invention also provides an insulator, comprising an insulator body and the high dielectric coating for improving flashover strength located on the surface of the insulator body.

[0022] Furthermore, the insulator body is one of a pot insulator, a post insulator or an insulator string.

[0023] Furthermore, the relative dielectric constant of the insulator body is 4, and the relative dielectric constant of the high dielectric coating for improving the flashover strength is 4-20.

[0024] Furthermore, when the insulator body is a pot-type insulator and a post insulator, it is used for metal-enclosed switchgear (GIS) and gas-insulated transmission pipeline (GIL) with rated voltages of 126 kV, 252 kV, 550 kV and 1100 kV; Furthermore, when the insulator body is an insulator string, it is used for overhead transmission lines with rated voltages of 110kV, 220kV, 500kV, 750kV and 1000kV.

[0025] In air at one atmospheric pressure, the surface flashover voltage of the insulator including the high dielectric coating for improving the flashover strength increases by at least 5.2% compared with the Weibull scale parameter of the surface flashover voltage of the insulator not including the high dielectric coating for improving the flashover strength; In air at three atmospheres, the Weibull scale parameter of the surface flashover voltage of the insulator including the high dielectric coating for improving the flashover strength increases by at least 13.8% compared with the Weibull scale parameter of the surface flashover voltage of the insulator not including the high dielectric coating for improving the flashover strength.

[0026] Furthermore, in air at one atmospheric pressure, the surface flashover voltage of the insulator including the high dielectric coating for improving the flashover strength is 24.89-27.82 kV; In air at three atmospheres, the surface flashover voltage of the insulator including the high dielectric coating for improving the flashover strength is 44.61-48.83 kV.

[0027] Furthermore, the raw material for preparing the bottom layer is the same as the raw material for preparing the insulator.

[0028] The present invention also provides a method for preparing the above insulator, comprising the following steps: Step 1, after the epoxy resin is stirred evenly to obtain a bottom layer solution, the bottom layer solution is evenly coated on the surface of the insulator body to obtain an insulator containing the bottom layer; Step 2, preparing cyanoethyl cellulose with different degrees of substitution by a homogeneous method and / or a heterogeneous method, respectively obtaining a first section of high-degree-of-substitution cyanoethyl cellulose, a second section of medium-degree-of-substitution cyanoethyl cellulose, and a third section of low-degree-of-substitution cyanoethyl cellulose; Step 3, dissolving the cyanoethyl cellulose with different degrees of substitution prepared in step 2 in organic solvents respectively to obtain a first top layer solution, a second top layer solution, and a third top layer solution; Step 4, coating the first top layer solution on the bottom layer near the triple junction formed by the electrode-solid-gas, and then coating the second top layer solution and the third top layer solution in sequence to obtain an insulator with the top layer coated on the bottom layer; Step 5: Dry the insulator obtained in step 4.

[0029] Furthermore, in step 2, the homogeneous method is to prepare cyanoethyl cellulose with different degrees of substitution by Michael addition reaction of cellulose solution and acrylonitrile, and the specific steps are as follows: The cellulose is dissolved in 1M sodium hydroxide / 6M urea solution to prepare a cellulose solution with a cellulose concentration of 5wt%; the cellulose solution is placed in an ice water bath, acrylonitrile is slowly added dropwise during stirring, and the reaction is continued for 10 hours; the reaction mixture is neutralized with acetic acid, and cyanoethyl cellulose is obtained after centrifugation and washing; wherein the cellulose is microcrystalline cellulose.

[0030] The degree of substitution is controlled by changing the molar ratio of glucose units to acrylonitrile in cellulose, such as the degrees of substitution are 1.5, 1.8, 1.9, and 2.0 when the molar ratios are 1:4, 1:6, 1:7, and 1:11.

[0031] Furthermore, in step 2, the heterogeneous method is to activate cellulose to obtain alkali cellulose, and the alkali cellulose undergoes Michael addition reaction with acrylonitrile to obtain cyanoethyl cellulose, and the specific steps are: The cellulose is dissolved in 1M sodium hydroxide / 6M potassium thiocyanate solution to prepare a cellulose solution with a cellulose concentration of 5wt%, and then filtered and squeezed dry. The obtained raw material is reacted with excess acrylonitrile for a certain period of time, and cyanoethyl cellulose is obtained after centrifugation and washing.

[0032] The degree of substitution is controlled by changing the reaction time of cellulose and acrylonitrile, such as when the reaction time is 70, 80, 90, 120, 200 min, the degrees of substitution are 1.7, 2.0, 2.2, 2.4, 2.7.

[0033] Furthermore, in step 3, the organic solvent is one of N,N-dimethylformamide, dimethylacetamide and dimethyl sulfoxide.

[0034] Further, the concentration of the first section of high-substituted cyanoethyl cellulose in the first top layer solution is 0.05-0.2 g / mL; The concentration of the substituted cyanoethyl cellulose in the second section of the second top layer solution is 0.05-0.2 g / mL; The concentration of the third stage low-substituted cyanoethyl cellulose in the third top layer solution is 0.05-0.2 g / mL.

[0035] Furthermore, the concentrations of cyanoethyl cellulose in the first top layer solution, the second top layer solution, and the third top layer solution are the same or different.

[0036] Furthermore, in step 5, the drying temperature is 80-100° C. and the drying time is 2-4 hours.

[0037] Furthermore, during the drying process of step 5, the high voltage electrode side of the insulator is placed downward, and under the action of gravity, a top layer structure is formed whose thickness gradually decreases from the high electric field area to the low electric field area.

[0038] Furthermore, continue coating on the top layer dried in step 5 to meet the thickness requirement during use. After each coating, drying is required before the next coating can be performed.

[0039] The present invention also provides an assembly structure, which comprises the above-mentioned insulator, a central high-voltage electrode and a grounding shell electrode.

[0040] The beneficial effects of the present invention are: 1. A high dielectric coating for improving flashover strength of the present invention, the high dielectric coating comprising a bottom layer and a top layer located outside the bottom layer, the top layer being a cyanoethyl cellulose layer, the raw materials for preparing the cyanoethyl cellulose layer comprising cyanoethyl cellulose with different degrees of substitution; wherein the degree of substitution of the cyanoethyl group in the cyanoethyl cellulose is 1-2.8, and the relative dielectric constant of the cyanoethyl cellulose layer is 4-20; the high dielectric coating prepared by the present invention adopts cyanoethyl cellulose with a gradually decreasing degree of substitution of the cyanoethyl group from a high electric field region to a low electric field region, so that the corresponding relative dielectric constant changes in a gradient manner, plays a role in uniformizing the electric field on the surface of the insulator, thereby effectively improving the surface flashover strength; That is, a pure polymer material with a flexibly adjustable dielectric constant is used. By coating polymer materials with successively decreasing relative dielectric constants in high, medium and low electric field regions, the electric field distribution can be made uniform, and the problems of local electric field distortion and reduced mechanical strength caused by filler doping can be effectively solved. 2. The present invention uses cyanoethyl cellulose with different degrees of substitution to adjust the relative dielectric constant. Cyanoethyl cellulose is a pure polymer material. Compared with the currently widely used method of increasing the dielectric constant by doping fillers, the method of the present invention does not have the problems of local electric field distortion and reduced mechanical strength caused by filler doping; 3. By coating the first section of high-substituted cyanoethyl cellulose with a high relative dielectric constant at the triple junction formed by electrode-solid-gas, the electric field intensity at the triple junction can be effectively reduced, thereby inhibiting the generation of gas discharge; 4. The high dielectric coating prepared by the present invention comprises a double-layer structure of a bottom layer and a top layer, and the bottom layer material is made of epoxy resin of the same material as the insulator body, so as to ensure that the coating can be well adhered to the insulator body; 5. The preparation process of the coating of the present invention is simple, and the coating method is suitable for insulator bodies with complex structures and suitable for large-scale production applications; it can effectively improve the surface flashover strength and guide the design and development of new functional gradient materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 It is a structural schematic diagram of an assembly structure including an insulator and an electrode; Figure 2 This is the electric field distribution diagram obtained by finite element simulation; Figure 3 Taking the high dielectric coating prepared in Example 1 as an example, a surface flashover voltage result diagram in pressurized air is shown; Figure 4 Taking the high dielectric coating prepared in Example 1 as an example, the surface flashover voltage results in air at three pressures are shown; Figure 5 Doped BaTiO 3 Electric field distribution simulation results of high dielectric constant filler materials; The labels in the figure are: 1. Bottom layer; 2. First section of high-substituted cyanoethyl cellulose layer; 3. Second section of medium-substituted cyanoethyl cellulose layer; 4. Third section of low-substituted cyanoethyl cellulose layer; 5. Central high-voltage electrode; 6. Grounding shell electrode; 7. Basin insulator. DETAILED DESCRIPTION

[0042] Example 1 like Figure 1 , which is a schematic structural diagram of an assembly structure including an insulator and an electrode, wherein the insulator includes an insulator body and a high dielectric coating located on the surface of the insulator body for improving flashover strength, the insulator body is a pot-type insulator 7, and the high dielectric coating includes a bottom layer 1 and a top layer located outside the bottom layer 1; the relative dielectric constant of the pot-type insulator 7 is 4; The bottom layer 1 is an epoxy resin layer, and the raw material for preparing the epoxy resin layer includes epoxy resin, and in this embodiment, it is bisphenol A glycidyl ether, which is the same material as the pot-type insulator 7, and is used to ensure that the bottom layer 1 can be well adhered to the pot-type insulator 7 body; The electrode assembly structure includes a central high-voltage electrode 5 and a grounded shell electrode 6.

[0043] The raw materials for preparing the epoxy resin layer also include a curing agent, methyl tetrahydroanhydride, and an accelerator, 2,4,6-triphenol. The curing temperature and speed of the epoxy resin can be adjusted by changing the content of the accelerator. In this embodiment, the mass ratio of the epoxy resin, the curing agent, and the accelerator is 10:8:1.

[0044] The top layer is a cyanoethyl cellulose layer, and the raw materials for preparing the cyanoethyl cellulose layer include cyanoethyl cellulose with different degrees of substitution; The substitution degree of cyanoethyl groups in cyanoethyl cellulose is 1.5-2.7, and the relative dielectric constant of the cyanoethyl cellulose layer is 6-18.

[0045] In this embodiment, the cyanoethyl cellulose layer is divided into three overlapping sections: a first section of a high-substituted cyanoethyl cellulose layer 2, a second section of a medium-substituted cyanoethyl cellulose layer 3, and a third section of a low-substituted cyanoethyl cellulose layer 4. The thickness of the first high-substituted cyanoethyl cellulose layer 2 is greater than the thickness of the second high-substituted cyanoethyl cellulose layer 3, and the thickness of the second high-substituted cyanoethyl cellulose layer 3 is greater than the thickness of the third low-substituted cyanoethyl cellulose layer 4.

[0046] The thickness of the high dielectric coating gradually decreases from the high electric field region to the low electric field region, that is, the thickness of the high dielectric coating gradually decreases from the first section high-substituted cyanoethyl cellulose layer 2 to the second section medium-substituted cyanoethyl cellulose layer 3, and then decreases from the second section medium-substituted cyanoethyl cellulose layer 3 to the third section low-substituted cyanoethyl cellulose layer 4.

[0047] In this embodiment, the maximum thickness of the top layer is 1 mm, and the thickness of the bottom layer 1 is 100 um.

[0048] Specifically, the degree of substitution of cyanoethyl groups in the first high-substituted cyanoethyl cellulose layer 2 is 2.7, and the relative dielectric constant is 18; In the second section, the degree of substitution of cyanoethyl groups in the cyanoethyl cellulose layer 3 is 2.2, and the relative dielectric constant is 12; The degree of substitution of cyanoethyl groups in the cyanoethyl cellulose in the third low-substituted cyanoethyl cellulose layer 4 is 1.5, and the relative dielectric constant is 6.

[0049] In this embodiment, the coating lengths of the first section high-substituted cyanoethyl cellulose layer 2, the second section medium-substituted cyanoethyl cellulose layer 3 and the third section low-substituted cyanoethyl cellulose layer 4 are equal.

[0050] The first section of the high-substituted cyanoethyl cellulose layer 2 is located at the triple junction formed by the electrode, the solid and the gas.

[0051] This embodiment also provides a method for preparing the above-mentioned insulator, comprising the following steps: Step 1, after the epoxy resin, curing agent and accelerator are uniformly stirred to obtain a bottom solution, the bottom solution is uniformly coated on the surface of the pot-type insulator 7 to obtain the pot-type insulator 7 containing the bottom layer 1, and the epoxy resin is given a certain room temperature curing ability by increasing the accelerator content to avoid the problem of easy flow after the epoxy resin is coated; Step 2, preparing cyanoethyl cellulose with different degrees of substitution by homogeneous method and heterogeneous method, respectively obtaining first-stage high-degree-substituted cyanoethyl cellulose, second-stage medium-degree-substituted cyanoethyl cellulose and third-stage low-degree-substituted cyanoethyl cellulose; In this embodiment, the first stage high-substituted cyanoethyl cellulose and the second stage medium-substituted cyanoethyl cellulose are activated by a heterogeneous method in the prior art to obtain alkali cellulose, and the alkali cellulose reacts with acrylonitrile to produce cyanoethyl cellulose by Michael addition reaction, and the specific steps are as follows: The cellulose is dissolved in a 1M sodium hydroxide / 6M potassium thiocyanate solution to prepare a cellulose solution with a cellulose concentration of 5wt%, and then filtered and squeezed to dryness, and the obtained raw material is reacted with excess acrylonitrile for a certain period of time, and then centrifuged and washed to obtain cyanoethyl cellulose; The degree of substitution is controlled by changing the reaction time of cellulose and acrylonitrile, and the degrees of substitution are 2.2 and 2.7 when the reaction time is 90 and 200 min; The third stage of low-substituted cyanoethyl cellulose is prepared by a homogeneous method in the prior art. The homogeneous method is to prepare cyanoethyl cellulose with different degrees of substitution by Michael addition reaction of cellulose solution and acrylonitrile. The specific steps are as follows: Dissolving cellulose in a 1M sodium hydroxide / 6M urea solution to prepare a cellulose solution with a cellulose concentration of 5wt%; placing the cellulose solution in an ice water bath, slowly adding acrylonitrile dropwise during stirring, and continuing the reaction for 10 hours; neutralizing the reaction mixture with acetic acid, centrifuging, and washing to obtain cyanoethyl cellulose; wherein the cellulose is microcrystalline cellulose; The degree of substitution is controlled by changing the molar ratio of glucose units to acrylonitrile in cellulose, and the degree of substitution is 1.5 when the molar ratio of the two is 1:4.

[0052] The degree of substitution of cyanoethyl cellulose prepared by homogeneous and heterogeneous methods is in the range of 1.5-2.7. Since cyanoethyl is a strongly polar group, it can enhance the dipole polarization strength of the material. Therefore, increasing the degree of substitution of cyanoethyl can effectively increase the relative dielectric constant of cyanoethyl cellulose, so that the relative dielectric constant can be flexibly adjusted between 6 and 18. By increasing the degree of substitution of cyanoethyl, the relative dielectric constant of cyanoethyl cellulose is higher than that of common polymer materials such as epoxy resin and polyvinylidene fluoride, and its relative dielectric constant is similar to that of BaTiO 3 The surface electric field intensity can be effectively reduced by using cyanoethyl cellulose as the coating material. Step 3, dissolving the cyanoethyl cellulose with different degrees of substitution prepared in step 2 in an organic solvent N,N-dimethylformamide respectively to obtain a first top layer solution, a second top layer solution, and a third top layer solution; The concentration of the first section of highly substituted cyanoethyl cellulose in the first top layer solution was 0.1 g / mL; The concentration of the substituted cyanoethyl cellulose in the second section of the second top layer solution was 0.1 g / mL; The concentration of the third low-substituted cyanoethyl cellulose in the third top layer solution was 0.1 g / mL; The concentration of cyanoethyl cellulose should not be too low. If it is too low, the viscosity of the mixed solution is insufficient, and the solution is easy to flow after being coated on the bottom layer 1. In addition, the concentration of cyanoethyl cellulose should not be too high. If it is too high, the viscosity is large and it is difficult to obtain a uniform coating. After many experimental comparisons, the most appropriate concentration of cyanoethyl cellulose is 0.1g / mL. Step 4, coating the first top layer solution on the bottom layer 1 including the triple junction point formed by the electrode, solid and gas, and then coating the second top layer solution and the third top layer solution in sequence, to obtain a pot-type insulator 7 with the top layer coated on the bottom layer 1; Step 5, drying the insulator obtained in step 4, the drying temperature is 90°C, and the drying time is 3 hours; during the drying process, the high-voltage electrode side of the pot-type insulator 7 is placed downward, and under the action of gravity, a top layer structure is formed whose thickness gradually decreases from the high electric field area to the low electric field area. From the perspective of uniform electric field, the use of dielectric constant functional gradient material can play a role in uniform electric field, and the gradient change structure of the top layer thickness also has a uniform electric field effect. Therefore, the top layer in the present invention is actually a dual gradient structure in which the relative dielectric constant and the coating thickness complement each other.

[0053] In some embodiments, coating is continued on the top layer dried in step 5 to meet the thickness requirement during use, and each coating needs to be dried before the next coating can be performed.

[0054] Through the above preparation and arrangement of the cyanoethyl cellulose coating, the relative dielectric constant of the top layer material gradually decreases from the high electric field region to the low electric field region, which plays a role in uniformizing the electric field on the surface of the insulator.

[0055] Comparative Example 1 This comparative example is a pot-type insulator 7 in Example 1 without the high dielectric coating.

[0056] Test Example 1 An insulator electric field distribution simulation model is established for the insulators in Example 1 and Comparative Example 1, including the steps of establishing an insulator geometric model, setting a material dielectric constant, setting boundary conditions, meshing, and finite element calculation. When establishing the insulator geometric model, the model is modeled according to the actual insulator and electrode dimensions, and the electric field strength is calculated according to the following equation:

[0057] In the formula, is the dielectric constant, E is the electric field strength, For the electric potential.

[0058] The high voltage electrode potential is set to 10 kV, the ground electrode potential is 0, the relative dielectric constant of the pot insulator 7 is 4, the relative dielectric constants of the first high-substituted cyanoethyl cellulose layer, the second medium-substituted cyanoethyl cellulose layer and the third low-substituted cyanoethyl cellulose layer in Example 1 are set to 18, 12 and 6 respectively, the simulation area is divided by quadrilateral mesh, and then the electric field distribution is calculated by finite element method. Figure 2 This is the electric field distribution diagram obtained by finite element simulation. A scaled-down basin insulator structure is used in the simulation. The figure compares the electric field distribution results of Comparative Example 1, which only contains an insulator body, and Example 1, in which a high dielectric coating is coated on the surface of the insulator body. It can be seen that the maximum electric field strength in Comparative Example 1 without a high dielectric coating is as high as 17.5 kV / cm, located near the central high-voltage electrode; when a high dielectric coating is added to Example 1, the peak electric field is reduced to 15.6 kV / cm. In addition, in Example 1, the high dielectric coating reduces the electric field strength throughout the entire surface area of ​​the insulator. The above results show that coating a high dielectric coating on the surface of the insulator body can even out the electric field distribution on the surface of the insulator, thereby improving the surface flashover strength.

[0059] Test Example 2 The flashover voltage of the insulators in Example 1 and Comparative Example 1 was tested at 0.5 kVs -1 The AC voltage is applied at a rising rate until flashover occurs, and the flashover voltage is analyzed using a two-parameter Weibull distribution. Figure 3 , Figure 4 , as shown in Table 1 and Table 2. Figure 4 Table 1 and Table 2 are the measurement results in air at one atmospheric pressure. It can be seen that the Weibull scale parameter of the surface flashover voltage of the insulator in Comparative Example 1 is 25.2 kV, and the Weibull scale parameter of the flashover voltage of Example 1 after coating with a high dielectric coating increases to 26.5 kV, with an increase of 5.2%; in addition, the flashover voltages of the nine experiments in Example 1 are generally higher than the flashover voltage of Comparative Example 1. Figure 5 Table 2 and Table 3 are the measurement results in air at three atmospheric pressures. The Weibull scale parameter of the surface flashover voltage of the insulator in Comparative Example 1 is 38.4 kV, and the Weibull scale parameter of the flashover voltage after the high dielectric coating is applied in Example 1 increases to 43.7 kV, with an increase of 13.8%; in addition, the flashover voltages of the nine experiments in Example 1 are all higher than the flashover voltage of Comparative Example 1. The above results show that the introduction of the high dielectric coating can effectively enhance the surface flashover strength of the gas-solid composite insulation system, mainly because the high dielectric coating plays a role in uniform electric field distribution.

[0060] Table 1 Flashover voltage of insulators with or without coating at one atmosphere (kV)

[0061] Table 2 Flashover voltage of insulators with or without coating at three atmospheres (kV)

[0062] Comparative Example 2 In order to explain the electric field distortion inside the material after doping with high dielectric constant fillers, an electric field distribution simulation model is established, including the steps of establishing a geometric model, setting the material dielectric constant, setting boundary conditions, meshing, and finite element calculation. The size of the simulation area is set to , 9 BaTiO 3 Filler, the electric field strength is calculated according to the following equation:

[0063] In the formula, is the dielectric constant, E is the electric field strength, For the electric potential.

[0064] The high voltage electrode potential was set to 0.45 V, the ground electrode potential was set to 0, the relative dielectric constant of the coating substrate area was 4, and the BaTiO 3 The relative dielectric constant of the filler is 975. The simulation results are as follows Figure 5 As shown, it can be seen that BaTiO 3 The electric field strength on the upper and lower sides of the filler increases significantly, indicating that BaTiO 3 Fillers will distort the electric field distribution in the coating matrix, and this electric field enhancement effect will reduce the surface flashover strength and breakdown strength.

[0065] In summary, the high dielectric coating prepared by the present invention uses cyanoethyl cellulose with a gradually decreasing degree of substitution of cyanoethyl groups from the high electric field region to the low electric field region, so that the corresponding relative dielectric constant decreases in a gradient, which plays a role in uniformizing the electric field on the surface of the insulator, thereby effectively improving the surface flashover strength; That is, by using a pure polymer material with a flexibly adjustable dielectric constant, and by coating polymer materials with successively decreasing relative dielectric constants in high, medium, and low electric field regions, the electric field distribution can be uniformed, and the problems of local electric field distortion and reduced mechanical strength caused by filler doping can be effectively solved.

[0066] In addition, the coating preparation process is simple, and the coating method is suitable for insulator bodies with complex structures and suitable for large-scale production applications; it can effectively improve the surface flashover strength and guide the design and development of new functional gradient materials.

[0067] It should be understood that the present invention is not limited to what has been described above and shown in the accompanying drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present invention is limited only by the appended claims.

Claims

1. A high dielectric coating for improving flashover strength, characterized in that: The high dielectric coating comprises a bottom layer and a top layer located outside the bottom layer; The bottom layer is an epoxy resin layer, and the raw materials for preparing the epoxy resin layer include epoxy resin; The top layer is a cyanoethyl cellulose layer, and the raw materials for preparing the cyanoethyl cellulose layer include cyanoethyl cellulose with different degrees of substitution; The substitution degree of cyanoethyl groups in cyanoethyl cellulose is 1-2.8, and the relative dielectric constant of the cyanoethyl cellulose layer is 4-20.

2. The high dielectric coating for improving flashover strength according to claim 1, characterized in that: The cyanoethyl cellulose layer is divided into three overlapping sections: a first section of a high-substituted cyanoethyl cellulose layer, a second section of a medium-substituted cyanoethyl cellulose layer, and a third section of a low-substituted cyanoethyl cellulose layer. The thickness of the first high-substituted cyanoethyl cellulose layer is greater than that of the second medium-substituted cyanoethyl cellulose layer, and the thickness of the second medium-substituted cyanoethyl cellulose layer is greater than that of the third low-substituted cyanoethyl cellulose layer.

3. The high dielectric coating for improving flashover strength according to claim 2, characterized in that: The degree of substitution of cyanoethyl groups in the first high-substituted cyanoethyl cellulose layer is greater than 2.4 and less than or equal to 2.8, and the relative dielectric constant is greater than 13 and less than or equal to 20; In the second section, the degree of substitution of cyanoethyl groups in the cyanoethyl cellulose layer is greater than 1.6 and less than or equal to 2.4, and the relative dielectric constant is greater than 7 and less than or equal to 13; The degree of substitution of cyanoethyl groups in the cyanoethyl cellulose in the third low-substituted cyanoethyl cellulose layer is greater than or equal to 1 and less than or equal to 1.6, and the relative dielectric constant is greater than or equal to 4 and less than or equal to 7.

4. The high dielectric coating for improving flashover strength according to claim 1, characterized in that: The raw materials for preparing the epoxy resin layer also include a curing agent.

5. An insulator, characterized in that: The insulator comprises an insulator body and a high dielectric coating for improving flashover strength according to any one of claims 1 to 4 located on the surface of the insulator body.

6. A method for preparing an insulator according to claim 5, characterized in that: The steps include: Step 1, stirring the epoxy resin to obtain a bottom layer solution, and coating the bottom layer solution evenly on the surface of the insulator to obtain an insulator containing the bottom layer; Step 2, preparing cyanoethyl cellulose with different degrees of substitution by a homogeneous method and / or a heterogeneous method, respectively obtaining a first section of high-degree-of-substitution cyanoethyl cellulose, a second section of medium-degree-of-substitution cyanoethyl cellulose, and a third section of low-degree-of-substitution cyanoethyl cellulose; Step 3, dissolving the cyanoethyl cellulose with different degrees of substitution prepared in step 2 in organic solvents respectively to obtain a first top layer solution, a second top layer solution, and a third top layer solution; Step 4, coating the first top layer solution on the bottom layer near the triple junction formed by the electrode-solid-gas, and then coating the second top layer solution and the third top layer solution in sequence to obtain an insulator with the top layer coated on the bottom layer; Step 5: Dry the insulator obtained in step 4.

7. The method for preparing an insulator according to claim 6, characterized in that: In step 3, the organic solvent is one of N,N-dimethylformamide, dimethylacetamide and dimethyl sulfoxide.

8. The method for preparing an insulator according to claim 6, characterized in that: The concentration of the first section of highly substituted cyanoethyl cellulose in the first top layer solution is 0.05-0.2 g / mL; The concentration of the substituted cyanoethyl cellulose in the second section of the second top layer solution is 0.05-0.2 g / mL; The concentration of the third stage low-substituted cyanoethyl cellulose in the third top layer solution is 0.05-0.2 g / mL.

9. The method for preparing an insulator according to claim 6, characterized in that: The drying temperature in step 5 is 80-100° C. and the drying time is 2-4 hours.

10. An assembly structure, characterized in that: The assembly structure comprises the insulator of claim 5, a central high voltage electrode and a grounded shell electrode.

Citation Information

Patent Citations

  • Nanometer-titania-doped polypropylene-based composite dielectric film used for film capacitors and preparation method of nanometer-titania-doped polypropylene-based composite dielectric film

    CN105038433A

  • Preparation method of surface conductivity gradient coating for direct current GIL epoxy resin insulator

    CN113793739A

  • Dielectric material composition and dispersion type el luminous element obtained from the same composition

    JP1991084024A

  • Highly dielectric cellulose derivative and its production

    JP1995126301A

  • Synthetic preparation method for cyanoethyl hydroxyethyl cellulose

    WO2018184145A1